Implementasi Pelatihan Menjahit sebagai Upaya Peningkatan Pendapatan Keluarga di Kecamatan Jabon melalui LKP Modes Flower Kabupaten Sidoarjo - Himatul Yufi Venrike; Rivo Nugroho (J+PLUS UNESA, 2023)
Sewing training through LKP Modes Flower Sidoarjo Regency to increase family income for the people of Jabon District, Sidoarjo Regency. The aim of the study was to find out the implementation of sewing training, the impact of sewing training on increasing family income, external and internal supporting factors, external and internal inhibiting factors. This research uses a qualitative approach with descriptive methods. The research subjects were Head of LKP Modes Flower, Sidoarjo Regency, instructors, learning residents. Data collection techniques are participant observation, in-depth interviews, documentation. Research data were analyzed using data collection, data condensation, data presentation, verification of conclusions then tested for its truth value with credibility, transferbility, dependability, confirmability. The results showed: (1) applying non-formal education in the implementation of sewing training, (2) residents learning after attending sewing training can increase family income, (3) external supporting factors for infrastructure are available, the government supports training activities and internal factors are the will of the residents' motivation learning, increasing the sewing talent of the learning residents, (4) external inhibiting factors where the training is limited, and internal factors completing homework before the training, not all learning residents have sewing talent.